Humoral COVID-19 vaccine response in patients with NMOSD/MOGAD during anti-IL-6 receptor therapy compared to other immunotherapies. (May 2023) - Schwake, Carolin; Pakeerathan, Thivya; Kleiter, Ingo; Ringelstein, Marius; Aktas, Orhan; Korporal-Kuhnke, Mirjam; Wildemann, Brigitte; Jarius, Sven; Bayas, Antonios; Pul, Refik; Ceylan, Ulas; Faissner, Simon; et al.
Background: Data on the humoral vaccine response in patients on anti-interleukin-6 (IL-6) receptor therapy remain scarce. Objective: The main objective of our study was to investigate the humoral response after vaccination against SARS-CoV-2 in neuromyelitis optica spectrum disorder (NMOSD)/myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) patients treated with anti-IL-6 receptor therapy. Secondarily, we analyzed relapse activity timely associated with vaccination. Methods: In this retrospective cross-sectional multicenter study, we included 15 healthy controls and 48 adult NMOSD/MOGAD patients without previous COVID-19 infection. SARS-CoV-2 spike protein antibody titers during anti-IL-6 receptor therapy were compared to anti-CD20 antibody therapy, oral immunosuppressants, and to nonimmunosuppressed individuals. Results: We observed 100% seroconversion in the anti-IL-6 receptor treatment group. Titers of SARS-CoV-2 spike protein antibodies were lower compared to healthy controls (720 vs 2500 binding antibody units (BAU)/mL, p  = 0.004), but higher than in the anti-CD20 (720 vs 0.4 BAU/mL, p  < 0.001) and comparable to the oral immunosuppressant group (720 vs 795 BAU/mL, p  = 1.0). We found no association between mRNA-based vaccines and relapse activity in patients with or without immunotherapy. Conclusions: Despite being lower than in healthy controls, the humoral vaccine response during anti-IL-6 receptor therapy was evident in all patients and substantially stronger compared to anti-CD20 treatment. No relevant disease activity occurred after mRNA vaccination against SARS-CoV-2.